Pemanfaatan Lahan Non-Produktif Sebagai Lahan Budidaya Tanaman Pangan Rumah Tangga di Kelurahan Prapen, Lombok Tengah - Muhammad Robby Rizky; Nanda Hikkal Wahyuni; Rini Srikus Saptaningtyas (Universitas Mataram, 2022)
The Sustainable Food House Program (RPL) implemented by the Tematic KKN Group at the University of Mataram is one of the concepts of using non-productive home gardens both in rural and urban areas to support national food security by empowering local food potential. Especially those around areas that have narrow land which makes it difficult for residents who live in the area to meet their basic needs, such vegetables and fruits which are included in staple consumption for residents, one of the efforts to overcome this is by sharing knowledge. Along with experiences with residents such as planting methods and other new methods or breakthroughs. The purpose of implementing this RPL program is to be able to utilize and optimize non-productive land to become productive, improve the family economy, meet family food and nutritional needs, and overcome waste problems.